Development of swelling pressure for pellet mixture and compacted block of GMZ bentonite. (27th September 2021) - Liu, Zhang-Rong; Ye, Wei-Min; Cui, Yu-Jun; Zhu, He-Hua; Wang, Qiong; Chen, Yong-Gui
Highlights: Swelling pressure and pore structure tests were conducted on pellet mixture and compacted block of GMZ bentonite. The final swelling pressures of the two specimens are similar while development kinetics are quite different. The difference was interpreted by competition between accumulated and dissipated wedging pressures. A porosity homogenization index was defined to describe the degree of homogenization of pore structure. Abstract: Bentonite pellet mixture is considered as a candidate buffer/backfill material for construction of artificial barrier in high-level radioactive waste (HLW) repository. Compared to that of a compacted bentonite block, one of the most obvious features of this material is its initially discrete pellets and significant structural heterogeneity, leading to a distinctive swelling behaviour. In this paper, a comparative study concerning development of swelling pressure on hydration was conducted on pellet mixture and compacted block of Gaomiaozi (GMZ) bentonite specimens with an identical dimensions (50 mm in diameter and 35 mm in height) and dry density (1.45 Mg/m 3 ). Results show that, within the initial 72 h, the swelling pressure of pellet mixture increases at a lower rate and achieves a lower peak value than those of the compacted bentonite block. Then, the swelling pressure of the pellet mixture varies slightly while that of the compacted bentonite block decreases significantly before increasing again. Eventually, the swelling pressure for the two specimens approaches to an almost similar final stable value, 0.939 MPa and 0.947 MPa, respectively. Based on an insight into the mechanism of swelling pressure development, a new theory on competition between the accumulated and dissipated wedging pressures (AWP and DWP) within the specimen was proposed for interpreting the different developments of swelling pressure between the two specimens. As water infiltrates, the AWP continuously increases, while the DWP firstly increases and then decreases. At a given infiltration time, the AWP of pellet mixture is smaller than that of compacted bentonite block due to accommodation of the pellets swelling deformation by inter-pellet voids. While within the initial hundreds hours of infiltration, the DWP within pellet mixture could be larger than that in compacted bentonite block due to the deformation (swelling or compression), damage (cracking or collapse) and displacement (rotation or dislocation) of the pellets. For both specimens, the macro and micro void ratios decrease while the meso void ratio increases with infiltration, leading to a gradually homogenized pore structure. Taking the pore size distribution curve of the middle layer of compacted bentonite block specimen after 720 h hydration as a reference, a porosity homogenization index ( PHI ) was defined to reflect the degree of pore structure homogenization. Generally, the PHI s of the upper, middle and lower part of the two specimens decrease with infiltration time. At a given time, the PHI s of pellet mixture are higher than those of compacted bentonite block but the difference between them decreases, leading to corresponding decrease of the swelling pressure difference. Considering the low swelling pressure (<1.0 MPa) of the current pellet mixture, it is necessary to improve its swelling capacity either by denser compaction or property modification for the safety of long-term operation of a HLW repository.